A Novel Homozygous ATP8A2 Variant in a Patient With Phenotypic Features of Dysequilibrium Syndrome - Amene Saghazadeh; Seyed Hassan Tonekaboni; Hossein Najmabadi; Nima Rezaei (Acta Medica Iranica, 2019)
The ATP8A2 protein is mainly located in the brain and takes part in the lipid flipping process. Mutations in the ATP8A2 gene and chromosomal translocations that interfere with the ATP8A2 gene product have been reported in association with global developmental delay and hypotonia. Here, we will report a three-year-old male presented with major phenotypic features of dysequilibrium syndrome (DES), including severe hypotonia, global developmental delay, speech problem, and strabismus. Whole exome sequencing revealed a homozygous in-frame deletion in the ATP8A2 gene (c.1286_1288delAGA, p.Lys429del). This ATP8A2 variant has not been reported yet and seems to be linked to the phenotypic features of dysequilibrium syndrome.